Analysis of relationship between Q-T and R-R interval inthe electrocardiogram of goats - MOHAN, N H; NIYOGI, DEBASISH; SINGH, H N (The Indian Journal of Animal Sciences, 2011)
To theoretically assure the complete electrical recovery of ventricular myocardium from one cardiac cycle before the next cycle begins the QT interval is corrected (QTc, corrected QT) with heart rate (HR). The present study was conducted to analyze the relationship between QT values and HR and utility of different formulae for QT correction. The study also describes QT interval index and QT dispersion in normal goats. Electrocardiographic data was obtained from 16 apparently healthy female goats. Corrected QT interval (QTc) was calculated as per Bazett`s formula, Friderica’s formula, by a linear formula (QTc=QT+0.154 (1-RR) and by optimization (QTc=QT/RR)0.299) and a modified Bazett`s formula (QTc=QT/(RR)0.6). The correlation studies (linear and polynomial-second degree) were made between QT and QTc calculated using different formulae. Among the various formulae for correction of QT interval the lowest correlation with RR was obtained by application of Bazett`s formula. The linear correlations were in the following descending order the Bazett`s modification>Bazett>Fridericia>Andrassy et al. >Sagie et al.> uncorrected QT-RR. The mean QT dispersion and QT interval index were 0.075±0.007 (range, 0.025 to 0.14) and 0.037±0.001 (0.032 to 0.056) respectively. The Bazetts`s correction with a slight modification theoretically reduced the influence of heart rate on QT interval. The QT dispersion and interval index was higher in goats that those reported for human subjects, suggesting more variability of the myocardium. However, further studies with a large cohort of animals are needed to analyze QT variation and its implication in wide-ranging clinical situations.